Pengaruh Environmental, Social, Dan Governance (ESG) Disclosure Terhadap Nilai Perusahaan (Studi Kasus pada Perusahaan Sektor Keuangan yang Terdaftar di Bursa Efek Indonesia Periode Tahun 2020 - 2023) - Nuraini, Azimatun; Nurhayati, Nurhayati; Adistie, Gisti Riza; Handayani, Alberta Esti (INVENTORY: JURNAL AKUNTANSI, 2025)
This study aims to determine the effect of environmental, social, and governance (ESG) disclosure on firm value in financial sector companies listed on the IDX (Indonesia Stock Exchange) for the period 2020-2023. This study uses quantitative data type with sample selection method using purposive sampling. This study used a sample of financial sector companies listed on the IDX (Indonesia Stock Exchange) during the period 2020-2023. The number of companies sampled in this study were 16 companies for 4 years with a total of 68 sample data. The data analysis techniques used in this study are descriptive analysis, classical assumption test, multiple linear regression analysis, and goodness of fit test. The results of this study indicate that environmental disclosure, social disclosure, and governance disclosure variables simultaneously have a significant impact on firm value.  Partial testing in this study shows that environmental disclosure has a partially significant effect on firm value, social disclosure variables have a partially significant effect on firm value, and governance disclosure variables have no partially significant effect on firm value. So it can be concluded that ESG disclosure has no significant effect partially on firm value.